Mass transfer in medium density fiberboard (MDF) modified by NA+ montmorillonite (NA+MMT) nanoclay - Zahedsheijani, Reza; Gholamiyan, Hadi; Tarmian, Asghar; Yousefi, Hossein (Maderas. Ciencia y Tecnología, 2025)
The potential use of nanoclay was examined to modify fluid transfer properties of medium density fiberboard (MDF). For this, Na+ montmorillonite (Na+MMT) nanoclay was added to urea formaldehyde resin to produce MDF. Then, the air permeability and mass diffusivity of MDF were evaluated. Scanning electron microscope (SEM) images and X-ray diffraction (XRD) confirmed a dispersion and exfoliation of Na+MMT in the modified MDF. The air permeability presented a systematic decrease with increasing nanoclay amount. This reduction agreed with the simple "tortuous path" model. The nanoclay had no effect on the mass diffusivity.